2002
DOI: 10.1017/s0266467402002389
|View full text |Cite
|
Sign up to set email alerts
|

Phenology and stem-growth periodicity of tree species in Amazonian floodplain forests

Abstract: To study the impact of the annual long-term flooding (flood- pulse) on seasonal tree development in Amazonian floodplains, the phenology and growth in stem diameter of various tree species with different leaf-change patterns were observed over a period of 2 y. The trees of the functional ecotypes, evergreen, brevi-deciduous, deciduous and stem-succulent showed a periodic behaviour mainly triggered by the flood-pulse. Trees have high increment during the terrestrial phase. Flooding causes a shedding of some or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
242
1
40

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 327 publications
(292 citation statements)
references
References 16 publications
9
242
1
40
Order By: Relevance
“…Our results are consistent with these findings, as those species showed no significant periodic structure in our analysis (table 1). In general, our data from herbarium specimens agree with field survey data, with one exception: our analysis detected no periodic pattern for C. latiloba, which is reported to have annual periodicity (table 1 [23]). …”
Section: Results (A) Flowering Frequencies In Climatic Regionssupporting
confidence: 85%
See 1 more Smart Citation
“…Our results are consistent with these findings, as those species showed no significant periodic structure in our analysis (table 1). In general, our data from herbarium specimens agree with field survey data, with one exception: our analysis detected no periodic pattern for C. latiloba, which is reported to have annual periodicity (table 1 [23]). …”
Section: Results (A) Flowering Frequencies In Climatic Regionssupporting
confidence: 85%
“…This conclusion is consistent with other studies that found annual periodicity in flower production in local populations, but with different flowering peaks throughout the year in different regions ( [16,25,27,28] Non-climatic factors may also affect Cecropia phenology. Cecropia latiloba is a highly flood-tolerant species widely distributed throughout the Amazon basin, for which Schöngart et al [23] found a high annual flowering periodicity in a population near Manaus. Data gathered from herbarium specimens for South Amazonia, however, suggest a non-annual pattern for this species (table 1).…”
Section: Discussion (A) Cecropia Flowering Frequenciesmentioning
confidence: 99%
“…In Brazil, dendrochronological/dendroclimatic studies are still incipient (Fritts, 1976;Schöngart et al, 2002Schöngart et al, , 2004Rigozo et al, 2007aRigozo et al, , b, 2008Lisi et al, 2008;Oliveira et al, 2009;Prestes et al, 2011Prestes et al, , 2014Andreacci et al, 2013;Pagotto et al, 2015;Lorensi and Prestes, 2016;Lorensi, 2016;Perone et al, 2016), considering the great biodiversity and continental dimension of Brazil when compared to South American countries such as Chile and Argentina. However, these kinds of studies have become more numerous in the recent years (Rigozo et al, 2007a(Rigozo et al, , b, 2008Lisi et al, 2008;Oliveira et al, 2009;Prestes et al, 2011Prestes et al, , 2014Andreacci et al, 2013;Pagotto et al, 2015;Lorensi and Prestes, 2016;Lorensi, 2016;Perone et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Parolin (2002) reporta o rápido crescimento caulinar na fase inicial da vida como maneira de aumentar a altura e escapar dos efeitos da submersão. Em termos de fenologia, algumas espécies decíduas como Albizia multiflora e Crataeva benthamii e semi-decíduas Alchornea castaneifolia e Luehea cymulosa apresentam a queda foliar total ou parcial em sincronia com o pulso de inundação Schöngart et al, 2002). E ainda, o crescimento de raízes adventícias é comumente observado em plântulas inundadas (Joly e Crawford 1982, Waldhoff et al, 1998Lopez e Kursar 2003;Parolin 2009), uma adaptação importante para absorção de oxigênio disponível na água.…”
Section: Introductionunclassified